Epidemiology of herpes zoster in National Guard Hospitals in Saudi Arabia: a 6-year retrospective chart review study - Farahat, Fayssal; AlZunitan, Mohammed; Alsaedi, Asim; Al Nassir, Wafa; Elgammal, Ayman; Nazeer, Syed; Althaqafy, Majid; El-Saed, Aiman; Al Enizi, Nouf; Hakami, Sulafah; Alsharef, Zainab; Guzman-Holst, Adriana; et al. (Frontiers in Public Health, 2025)
IntroductionIncidence of herpes zoster (HZ) is increasing worldwide, imposing significant burden on healthcare resources. In Saudi Arabia, local epidemiological studies are limited, and HZ burden is unknown.MethodsThis multi-center, hospital-based, retrospective medical chart review was conducted at five National Guard hospitals and affiliated primary care centers. Patients included military personnel, healthcare workers, and family dependents, in addition to non-eligible individuals via referral from other healthcare systems. Data were retrospectively collected from electronic medical records of documented cases of HZ or related complications from January 2017–December 2022.Results1,019 HZ cases were identified, with the number of cases increasing annually (2017: 89; 2022: 279). Estimated HZ prevalence over the study period was 0.12%. Mean age of patients was 52.8 years and >50% were females. Most (73.9%) patients had ≥1 comorbidity, most commonly hypertension (38.9%) and diabetes (37.7%). HZ-related complications were detected in 31.3% of cases; post-herpetic neuralgia was diagnosed in 17.6% and disseminated HZ in 5.6% of patients. In total, 12.5% of patients were hospitalized; 1.2% required intensive care unit admission. Mean hospital stay was 10.1 days. Use of antiviral medications was reported in most cases (87.5%). Significant predictors of complicated HZ, identified via multivariable logistic regression analyses, were age ≥60 years (odds ratio=1.42; p=0.03), autoimmune disease (2.45; p<0.01), depression (2.68; p=0.02), and chronic lung disease (1.95; p=0.04).ConclusionThis study provides updated insights into HZ epidemiology in Saudi Arabia. A high proportion of patients identified in a hospital setting with HZ had comorbidities and a substantial proportion experienced complications.